PERENCANAAN PERLUASAN APRON MENGGUNAKAN KONSTRUKSI RIGID DI TERMINAL BARU BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Danesia Raka Panduwinata; Sukamto; Luky Surachman (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
Ahmad Yani International Airport Semarang located in West side of Semarang and managed by PT. Angkasa Pura I (Persero) which serves domestic and international flights. With the high airplane movements during peak hours, it is feared that there will be a waiting time between airplanes that will be landing because of the lack of apron capacity. In order to support the smoothness, the apron necessary to be expanded to accommodate all aircraft movements during peak hours. Therefore, this final project made for present how to plan the expansion and standard pavement thickness of the apron in accordance with the International Civil Aviation Organization (ICAO). According to the result of the calculation, the development of the planned apron dimensions is 820 x 131,5 m for the addition of 20 parking stand and obtained the overall pavement thickness of the apron is 64.8 cm. Including 39.4cm of concrete slab thickness with K-400 concrete quality and subbase 25.4 cm to subgrade with CBR 6%.